(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2014)
Urban marketing has recently been adopting the concept, and the label, of “second city”. However, this concept requires sharper theoretical definition in order to turn heuristic. Thus far, it has been conceived in relation to an “ideology of ranking”, strictly related to the worldview of post-modern globalization. A more fruitful definition of “second cities” results from Charles S. Peirce’s idea of secondness: a city is second to another not in quantitative, but in qualitative and relational terms. The semiotic model of Jurij M. Lotman offers a suitable methodology to analyse this relational definition, as it is exemplified by the case-study of the rivalry between Melbourne and Sydney. A historical survey of their relation shows that the latter progressively embraced an identity of “secondness” so as to successfully market an alternative vision of urban life. Melbourne therefore provides a model for non-quantitative construction of urban distinctiveness.